PENGARUH LINGKUNGAN SEKOLAH TERHADAP PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN 009 MESAH - Arfan, Arfan (Cahaya Ilmu Bangsa Institute, 2024)
This research aims to analyze the influence of the school environment on Islamic Religious Education (PAI) learning at SDN 009 Mesah. The school environment is considered an important factor that influences the effectiveness of learning, including in Islamic Religious Education subjects. This research uses a descriptive qualitative method, which allows researchers to explore and describe the phenomena that occur in depth and detail. Data was collected through observation, in-depth interviews with teachers and students, as well as analysis of documentation related to learning programs at schools. A conducive school environment includes physical and non-physical aspects. This will have a positive impact on the PAI learning process and outcomes at SDN 009 Mesah. Physical aspects include adequate learning facilities and comfortable classrooms, while non-physical aspects include a school culture that supports Islamic values and harmonious relationships between teachers and students. It is hoped that the research results will provide a more comprehensive understanding of how the school environment can influence the quality of PAI learning, as well as suggest strategies and policies that can be implemented by schools to increase the effectiveness of PAI learning. Thus, it is hoped that this research can contribute to the development of theory and practice in the field of Islamic religious education, especially in the context of elementary schools in Indonesia. This research can also be a reference for other educational institutions that seek to improve the quality of Islamic religious education through better management of the school environment.